Prevalence and correlates of depressive symptoms and competitive anxiety in tennis players: a cross-sectional study - Marc Niering; Emilia Richter; Julius Riedel; Rainer Beurskens; Johanna Seifert (Frontiers in Public Health, 2026)
Background Tennis is a psychologically demanding individual sport characterized by high competitive pressure and self-regulatory demands. However, data on depressive symptoms and competitive anxiety in tennis players remain limited. Objectives To assess the prevalence of depressive symptoms and competitive anxiety in active tennis players and identify demographic and sport-related correlates. Methods In this cross-sectional online survey, 313 active tennis players (mean age 26.9 ± 10.2 years) completed the Beck Depression Inventory-II (BDI-II) and the Sport Competition Anxiety Test (SCAT). Associations between psychological outcomes and demographic and sport-related variables were examined using correlation and regression analyses. Results Clinically relevant depressive symptoms were reported by 33.5% of participants. Female athletes reported higher competitive anxiety than male athletes ( p = 0.003). Competitive anxiety was positively associated with depressive symptoms ( r = 0.119, p = 0.036). A previous diagnosis of depression was the strongest predictor of clinically relevant depressive symptoms ( OR = 6.81, 95% CI [2.22, 20.91]). Previous depression diagnosis, recent injury or illness, and psychotropic medication use were associated with greater depressive symptom severity. Conclusion Competitive tennis players demonstrated a substantial burden of depressive symptoms and competitive anxiety, with one third of athletes reporting clinically relevant depressive symptoms. Competitive anxiety was associated with depressive symptoms, indicating overlapping aspects of psychological distress. Athletes with a history of depression, recent injury or illness, or psychotropic medication use may represent groups with an increased burden of depressive symptoms and may benefit from closer monitoring. Routine mental health screening, integrated psychological support, and targeted interventions during injury rehabilitation should be considered to promote athlete well-being and reduce persistent psychological distress.